PENGARUH BUDAYA KESELAMATAN KERJA, KEPIMIMPINAN DAN MOTIVASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA PERUSAHAAN MINYAK DAN GAS BUMI â€œXâ€ DI PROPINSI KALIMANTAN TIMUR - Marzuki, Hasan; Sularso, Raden Andi; Purbangkoro, Murdijanto (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Abstract: Research on corporate culture has been widely conducted both in Indonesia and overseas. However, research focuses on occupational health and safety (OHS) culture has not gained much attention in Indonesia, especially related to leadership, job satisfaction, motivation, and employee performance. This research aimed to analyze the influence of OHS culture, leadership, and motivation on job satisfaction and employee performance in the â€œXâ€ oil and gas company in East Kalimantan Province. Primary data were collected from the sample consisted of 290 respondents, i.e, the permanent employees and the contractorâ€™s employee working at Hindi II base. Results showed that OHS culture had a significant influence on job satisfaction, but it had no influence on employee performance. Leadership had a significant influence on job satisfaction and employee performance. Motivation had a significant influence on job satisfaction and employee performance. Job satisfaction had a significant influence on employee performance. Keywords: OHS Culture, Leadership, Motivation, Job Satisfaction, Employee Performance.